Point-of-care HIV testing best practice for early infant diagnosis: an implementation study - Elizabeth Spooner; Kerusha Govender; Tarylee Reddy; Gita Ramjee; Noxolo Mbadi; Swaran Singh; Anna Coutsoudis (BMC, 2019)
Abstract Background With Universal Health Coverage and Integrated People-centred Health Care, streamlined health-systems and respectful care are necessary. South Africa has made great strides in prevention of mother-to-child transmission (PMTCT) but with the great burden of HIV, a minimum of birth and 10-week HIV-PCR testing are required for the estimated 360,000 HIV-exposed infants born annually which presents many challenges including delayed results and loss to follow-up. Point-of-care (POC) HIV testing of infants addresses these challenges well and facilitates initiation of HIV-infected infants rapidly after diagnosis for best clinical outcomes. Methods Objectives were to determine accuracy, feasibility and acceptability of POC testing compared to standard-of-care (SOC) central-laboratory testing. HIV-exposed infants for birth PCR testing in hospital (n = 323) and follow-up at a primary health care clinic (n = 117) in Durban, South Africa were included. A baseline situational-analysis reviewed registers and phoned mothers of HIV-exposed infants prior to the intervention. An effectiveness-implementation study of the Alere™q HIV-1/2 Detect POC test (heel-prick specimen processed in 50 min) was compared with SOC with questionnaires to mothers and staff. Stata 14 was used for analysis. Results At baseline 2% of birth HIV tests were missed; only 40% of mothers could be contacted; 17% did not receive birth test result; 19% did not have a 10-week test; 39% had not received the 10-week results. There were 5(1.5%) HIV-infected and 318(98.5%) HIV-negative infants detected in hospital with all clinic babies negative. All positive infants commenced ART before discharge. Ultimately POC and SOC had perfect concordance but for 10 SOC tests researchers actively tracked-down results or repeated tests. Turn around times for SOC tests were on average 8-days (IQR 6-10  days) and for POC testing was 0-days. The POC error-rate was 9,6% with all giving a result when repeated. The majority of mothers (92%) preferred POC testing with 7% having no preference. No staff preferred SOC testing with 79% preferring POC and 21% having no preference. Conclusions Point-of-care HIV testing for EID is accurate, feasible and acceptable, with benefits of early ART for all positive infants at birth facilities. We recommend that it be considered best practice for EID. Trial registration ISRCTN38911104 registered 9 January 2018 - retrospectively registered.